EVALUATION OF SEASONAL TEMPERATURE AND HUMIDITY CHANGES ON BLOOD METABOLITES OF KANO BROWN BUCKS - Nasir, M.; Aliyu, Abduljalal M.; Abdulhamid, Sulaiman Umar; Sariyyu, S.; Kakudi, Ismail A. (FUDMA JOURNAL OF SCIENCES, 2025)
Small and large ruminants are often negatively affected by heat stress when the environmental temperature exceeds the upper critical level of 48°C. This condition can lead to decreased production and weight gain in the animals. The aim of this study was to evaluate the effects of seasonal temperature and humidity changes on blood metabolites of Kano Brown bucks. Small and large ruminants are often be affected negatively by heat stress when the environmental temperature exceeds the upper critical level of 48 0 C, it is also result in decrease in production and weight gain of the animals. The study was conducted to evaluate the effect of seasonal temperature and humidity changes on blood metabolites of Kano brown bucks during the periods of dry season (March to June, 2016) in Sudan Savannah region of Nigeria. Sixteen bucks were allotted to four treatments in complete randomized block design with four animals each per treatment. Baseline data was obtained at the end of experiment. The result obtained for Hb, PCV, MCHC, MCH, WBC, lymphocytes and monocytes mean values did not differed statistically (P > 0.05) whereas RBC, Neutrophils and Basophils differed significantly (p < 0.05). Blood serum chemistry and cortisol hormone differed (P > 0.05). The result indicates that temperature between 280C – 460C doesn’t have any detrimental effect on hematological parameters, blood serum chemistry and cortisol hormone of Kano brown bucks.
Keywords: Blood metabolites; Evaluation; Humidity; Kano brown bucks; Seasonal temperature